Molecular Characterization of the Lipid Genome-Wide Association Study Signal on Chromosome 18q11.2 Implicates HNF4A-Mediated Regulation of the TMEM241 Gene. Issue 7 (July 2016) - Rodríguez, Alejandra; Gonzalez, Luis; Ko, Arthur; Alvarez, Marcus; Miao, Zong; Bhagat, Yash; Nikkola, Elina; Cruz-Bautista, Ivette; Arellano-Campos, Olimpia; Muñoz-Hernández, Linda L.; Ordóñez-Sánchez, Maria-Luisa; Rodriguez-Guillen, Rosario; et al.
Abstract : Objective—: We recently identified a locus on chromosome 18q11.2 for high serum triglycerides in Mexicans. We hypothesize that the lead genome-wide association study single-nucleotide polymorphism rs9949617, or its linkage disequilibrium proxies, regulates 1 of the 5 genes in the triglyceride-associated region. Approach and Results—: We performed a linkage disequilibrium analysis and found 9 additional variants in linkage disequilibrium ( r 2 >0.7) with the lead single-nucleotide polymorphism. To select the variants for functional analyses, we annotated the 10 variants using DNase I hypersensitive sites, transcription factor and chromatin states and identified rs17259126 as the lead candidate variant for functional in vitro validation. Using luciferase transcriptional reporter assay in liver HepG2 cells, we found that the G allele exhibits a significantly lower effect on transcription ( P <0.05). The electrophoretic mobility shift and ChIPqPCR (chromatin immunoprecipitation coupled with quantitative polymerase chain reaction) assays confirmed that the minor G allele of rs17259126 disrupts an hepatocyte nuclear factor 4 α–binding site. To find the regional candidate gene, we performed a local expression quantitative trait locus analysis and found that rs17259126 and its linkage disequilibrium proxies alter expression of the regional transmembrane protein 241 ( TMEM241 ) gene in 795 adipose RNAs from the Metabolic Syndrome In Men (METSIM) cohort ( P =6.11×10 −07 –5.80×10 −04 ). These results were replicated in expression profiles of TMEM241 from the Multiple Tissue Human Expression Resource (MuTHER; n=856). Conclusions—: The Mexican genome-wide association study signal for high serum triglycerides on chromosome 18q11.2 harbors a regulatory single-nucleotide polymorphism, rs17259126, which disrupts normal hepatocyte nuclear factor 4 α binding and decreases the expression of the regional TMEM241 gene. Our data suggest that decreased transcript levels of TMEM241 contribute to increased triglyceride levels in Mexicans. Abstract : Supplemental Digital Content is available in the text.